The Effect of Tax Planning, Profitability, and Carbon Emission Disclosure on Firm Value - Yenni Vera Fibriyanti; Indah Kurniyawati; Rochman Arif (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the effect of tax planning, profitability, and carbon emission disclosure on firm value in basic materials sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sampling technique employed was purposive sampling. Based on the established criteria, 31 companies were selected, resulting in 124 research observations. The results indicate that tax planning and profitability have a positive and significant effect on firm value, whereas carbon emission disclosure does not have a significant effect on firm value. Furthermore, the findings reveal that tax planning, profitability, and carbon emission disclosure simultaneously have a significant effect on firm value.